2004
DOI: 10.1074/jbc.m314235200
|View full text |Cite
|
Sign up to set email alerts
|

Group IB Secretory Phospholipase A2 Promotes Matrix Metalloproteinase-2-mediated Cell Migration via the Phosphatidylinositol 3-Kinase and Akt Pathway

Abstract: Secretory phospholipase A 2 (sPLA 2 ), abundantly expressed in various cells including fibroblasts, is able to promote proliferation and migration. Degradation of collagenous extracellular matrix by matrix metalloproteinase (MMP) plays a role in the pathogenesis of various destructive disorders, such as rheumatoid arthritis, tumor invasion, and metastasis. Here we show that group IB PLA 2 increased pro-MMP-2 activation in NIH3T3 fibroblasts. MMP-2 activity was stimulated by group IB PLA 2 in a dose-and time-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 43 publications
(38 reference statements)
4
34
0
Order By: Relevance
“…These data suggested that CD9 modulated MMP-2 production of blastocysts cultured on FN via the PI3K signaling pathway. This result is in agreement with studies of MMP-2 in NIH3T3 and MDA-MB-231 cells (Sugiura & Berditchevski 1999, Choi et al 2004.…”
Section: Discussionsupporting
confidence: 82%
“…These data suggested that CD9 modulated MMP-2 production of blastocysts cultured on FN via the PI3K signaling pathway. This result is in agreement with studies of MMP-2 in NIH3T3 and MDA-MB-231 cells (Sugiura & Berditchevski 1999, Choi et al 2004.…”
Section: Discussionsupporting
confidence: 82%
“…Many reports, including our study, have shown that PI3K/ Akt pathway is critically involved in MMP-2 expression (19,(42)(43)(44). However, none of these studies revealed the relationship between PI3K/Akt signaling pathway and AP-2 activation.…”
Section: Discussionmentioning
confidence: 47%
“…Numerous reports have demonstrated that MMP-2 expression is critically mediated by MAPK members 13,15) and PI3K/Akt pathway. 23,33,34) MAPK and PI3K/Akt pathways also play an important role in endothelial cell viability, migration, and tube formation by specific stimuli. [13][14][15]25,35,36) Therefore, we examined the effect of a-chaconine on the activities of MAPK and PI3K/Akt signaling pathways.…”
Section: Fig 3 Effect Of A-chaconine On Chemotaxis and Invasion Of mentioning
confidence: 99%